Patient Understanding of Diabetes Self-Management: Participatory Decision-Making in Diabetes Care - Quinn, Charlene C (Diabetes Technology Society, 2011)
OBJECTIVE: Our aim was to determine whether patient participation in decision-making about diabetes care is associated with understanding of diabetes self-management and subsequent self-care practices. We also identified issues that would impact messaging for use in mobile diabetes communication. RESEARCH DESIGN AND METHODS: A cross-sectional observational study was conducted with type 2 diabetes patients (n = 81) receiving their care at the University of Maryland Joslin Diabetes Center. A convenience sample of patients were eligible to participate if they were aged 25–85 years, had type 2 diabetes, spoke English, and visited their physician diabetes manager within the past 6 months. In-person patient interviews were conducted at the time of clinic visits to assess patient understanding of diabetes management, self-care practices, and perceptions of participation in decision-making about diabetes care. RESULTS: African Americans reported fewer opportunities to participate in decision-making than Caucasians, after controlling for education [mean difference (MD) = -2.4, p = .02]. This association became insignificant after controlling for patient–physician race concordance (MD = -1.5, p = .21). Patient understanding of self-care was predicted by having greater than high school education (MD = 3.6, p = .001) and having physicians who involved them in decision-making about their care. For each unit increase in understanding of diabetes self-care, the mean patient self-care practice score increased by 0.16 (p = .003), after adjustment for patient race and education. CONCLUSIONS: Patient participation in decision-making is associated with better understanding of care. Participation in decision-making plays a key role in patient understanding of diabetes self-management and subsequent self-care practices. Patients with limited education need specific instruction in foot care, food choices, and monitoring hemoglobin A1c.